(untitled) (Eurasian Scientific Herald, 2023)
In our article, science fiction is the study of complex topics and concepts that have attracted readers and film fans for generations, offering imaginative visions of the future. In science fiction, there are different sub-genres, each with its own artistic characteristics that distinguish it from the others. This essay makes a thorough study of some artistic peculiarities of the most well-known science fiction genre, namely dystopian, cyberpunk, and space opera